The cognitive executive functions of distinguished students (Journal of the College of Basic Education, 2022)
: The research aims to identify Knowing the cognitive executive functions of distinguished students 1- 1- Differences in executive jobs according to the gender variable (male-female) The current research is limited to students of distinguished schools in the Holy Karbala and Babil governorates, and the sample consisted of (400) male and female students, which included four schools and for two stages, the fourth scientific and the fifth biological for the academic year (2020-2021) by (200) students for the fourth scientific grade and (200) A male and female student of the fifth grade of biology, and the research used a measure tool for executive cognitive functions prepared by researchers, and it consists of (50) items distributed into four areas: (mental flexibility, spotting, organization, and self-monitoring). The psychometric properties were extracted from honesty, constancy and distinctive power. For the paragraphs and the relationship of the paragraph score to the overall score of the scale and the relationship of the paragraph score to the degree of field and the extraction of stability by testing and retesting, the scale stability coefficient reached (0.923). As for the statistical methods, the researcher used the Statistical Package for Psychosocial Sciences (SP-SS) program to process the data, and the results showed the following: 1-The distinguished students enjoy a level of executive and cognitive functions 2-There are no differences in the cognitive executive functions among them. Distinguished students according to the gender variables. According to the results of the current research, some recommendations and proposals have been crystallized.